The Knowledge Economy and the Activation of Scientific and Technological Progress: Contemporary Challenges - Melnikas, Borisas (Ekonomika, 2018)
This article is dedicated to the problems and processes of the activation of scientific and technological progress in the context of contemporary challenges of the creation of a knowledge-based society and knowledge economy. The main focus here is on activating innovations, scientific and technological progress and creating various preconditions for the development of a knowledge-based society and knowledge economy.The contemporary processes and phenomena of innovations of scientific and technological progress and of its activation are analyzed in a complex manner; the needs for the purposeful activation and acceleration of scientific and technological progress, in particular in response to the aspirations of the knowledge-based society and the creation of a knowledge economy, are investigated in the presented material.The role and importance of innovation activities and the acceleration of scientific and technological advance in the context of the creation of a knowledge-based society and a knowledge economy are revealed and highlighted. New ideas of the search and use of synergetic effects, as well as a new theoretical approach based on the so-called universal principle of the creation of a “new quality,” are described.The results of the presented research can be used for preparing practical recommendations and methodologies that could be applied in the creation and implementation of the managerial and economic instruments and support systems aimed at the purpose of activating the processes of innovations and scientific and technological progress. These recommendations and methodolies could also be utilized in the development of international relations in the context of what is required in the creation of a knowledge-based society and knowledge economy.It is shown that the problems and processes of scientific and technological progress can be appreciated as an extremely important and viable field of scientific research on the creation and development of a knowledge economy.Keywords: knowledge economy, scientific and technological progress, innovation, synergy, networking
Keywords: knowledge economy, scientific and technological progress, innovation, synergy, networking